THE IMPACT OF THE 2009 INDONESIA’S DIVIDEND TAX CUT ON DIVIDEND PAYMENT - I Wayan Agus Eka (Politeknik Keuangan Negara STAN, 2018)
On January 1, 2009 the effective tax rate for individual-recipient dividend fell significantly from 35% to 10%. This paper investigated the impact of the dividend tax cut policy on dividend payment in three aspects i.e. extensive margin, intensive margin and dividend per share amount, an adoption from Chetty and Saez (2004) approach. I used publicly available data provided by The Indonesian Stock Exchange and The Indonesian Central Securities Depository. I found that one year after the tax cut policy, the fraction of the firms paying dividend increase and reach its peak in 2011. From intensive margin approach, the percentage of firms that increase their dividend per share amount also increase one year after the policy. Using regression analysis, this paper also found that the tax cut policy increased the dividend per share amount by 35.03. This study, to my knowledge, provides the first empirical evidence of the effect of dividend tax cut policy and concludes that the policy has positive impact on dividend payment in term of fraction of firms paying dividend, fraction of firms increasing their dividend and the nominal amount of the dividend per share.